Eyalet of Kurdistan in the Ottoman Salanams : (1847-1867) - Lezan Zrar Fathulla (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research is in order to shed light on the history of the Kurdistan Ayalah through the administrative division by the Ottoman Empire, and the reasons for its formation. The geographical area that the Ottoman Empire had had its reasons for selecting those areas under the administration for a specific mandate, and how to distribute its administrations into districts, districts, districts and villages belonging to them. From here comes the importance of the salnames, according to which official documents are considered an important historical source, and the salname is a great source of information, data and important statistical data about the Ottoman provinces. The salnames also dealt with the names of the governors who were appointed in the Eyalet of Kurdistan and the military princes in charge of managing the military centers and sites in the wilaya, with mention of senior officials and official titles circulated in official circles. The study also referred to some social, cultural and scientific aspects, especially with regard to those in charge of endowments and their academic degrees, and Al-Salammah mentioned in its various issues the names of these and other employees in the administration of the Judicial Council. Besides these there were employees who handled financial matters and accountants. The research also referred to the religious sects, such as the Christians who lived in the Ayala of Kurdistan, and how they were distributed among the Patriarchate according to the sects in their churches in the districts and districts, by arranging their class in the centers belonging to any district of the district churches.